University Students’ Perspective on Material and Activities in English Listening Class During Pandemic - Nurkhamidah, Neni (Universitas Lancang Kuning, 2021)
The most obvious impact of Covid-19 in the education field is the shifting of face-to-face classroom meetings into online learning. Since fully online learning is new for most universities in Indonesia, teachers have to abruptly prepare effective learning material and activities to support student learning in distance. Several studies on listening classes in Indonesia have been carried out during the Covid-19 pandemic, but studies that focus on student’s perspectives on the material and activities in English listening class in higher education have not been conducted yet. This study fills this research gap because students’ perspectives are important to improve the quality of listening-focused courses. This study is conducted on January 2021 by involving nine English Education students enrolled in the Basic Listening class at the STKIP Media Nusantara Citra. Questionnaires and interviews are employed to collect qualitative data. Despite the abruptness of creating and adapting new materials with an unfamiliar learning style, results showed that students have a positive perspective toward the effect of the lecturers’ materials on their learning motivation, the usefulness of the material, the level of difficulty and quantity of the material and activities, the variety of material and activities, the usefulness of pre- and post-listening activities, the quality of audio and the suitability of worksheet.